ANTI-INFLAMMATORY, ANTIHYPOXANT AND ANTIOXIDANT ACTIVITY OF PRODUCTS ISOLATED FROM CAPER CULTIVATED IN UZBEKISTAN - Bekmurzayeva Nurjamal Baxtiyarovna; Botirov Ruzali Anvarovich; Azamatov Azizbek Azamatovich; Tursunkhodzhaeva Firuza Muratovna; Aytbaeva Aygul Baxtiyarovna; Sadykov Alimdjan Zairovich; Sagdullayev Shamansur Shaxsaidovich (The Bioscan, 2024)
Caper extracts have been reported to possess antibacterial, antifungal, analgesic, antitumor, hepatoprotective, antioxidant, anti-inflammatory, and neuroprotective effects. We have isolated polysaccharide and protein sums from buds and fruits of C.spinosa L. cultivated in Uzbekistan. The goal of this research was to investigate anti-inflammatory activity of isolated sums in comparison with ketoprofene. The experiments were made using the formalin-induced paw edema in mice in three variations, at first the investigated substances were introduced to rats per os once, and at the second and third experiment the investigated substances were introduced to the animals for five and ten days. On hemic hypoxia model the investigated substances shown high antixypoxic effects close to Mildronate neo drug (70.7%) at doses of 25 mg/kg for PPSCB (67%) and 150 mg/kg for PPSCF (64.2%). On cytotoxic hypoxia model the effects of both investigated substances also were relatively high and close to Mildronate neo (61%), PPSCB – 56% at a dose of 50 mg/kg, and PPSCF – 58% at a dose of 150 mg/kg. In normobaric hypoxia effects of all investigated substances were less, including the etalon drug (25.4%), PPSCB – 25.5% at dose of 150 mg/kg and PPSCF at 100 mg/kg – 29%. The influence of investigated substances on SOD activity has been investigated. It was established that the both investigated sums at first minute of the test increase SOD activity for PPSCB at a dose of 50 mg/kg by 2.28 times, and PPSCF at a dose of 150 mg/kg by 2.26 times in compare to the control. These results indicated on the increasing of antioxidant protection and improving the oxidative status of experimental animals. Thus, the carried out investigation results shown the high anti-inflammatory, antihypoxic and antioxidant potential of PPSCF and PPSCB products. In combination with their low toxicity these properties make them good candidates for development of effective therapeutic remedies and food additives.